Pengembangan Digital Library Universitas Bina Darma Menggunakan Pendekatan Human Computer Interaction - Kurniati Kurniati (Ikatan Ahli Informatika Indonesia (IAII), 2018)
Bina Darma University has implemented a digital library which is located in http://digilib.binadarma.ac.id. With this facility, it will be easier for students, faculty, and visitors to obtain information relating to digital documents such as journals, theses or other library activities. However, application of digital library Bina Darma University in Palembang assessed not maximized because of the small number of visitors who use these facilities and prefer to search digital documents such as journals by search engines as a source of information. Human Computer Interaction (HCI) approach method can be used to create a system and within their right to the user. In addition, to facilitate the development, paper prototype method helps in the design of a more complete according to user needs. So, will result in generating a new design that can increase the interest of visitors to access digital library Universitas Bina Darma Palembang as the main alternative in the search for information and as a self-development.